A Study On The Influence Of Belief Factors And Demographic Characteristics On The Attitudes Toward Web Advertising Among USM Staff In Penang - MOHD IZZUDDIN, IZRA AZLIANA (2004)
The majority of research about Web advertising has been conducted in Western countries. However, little is known about Web users’ attitudes toward Web advertising in Malaysian context. This study, conducted in Penang, Malaysia to examine Web users’ attitudes toward Web advertising is tested by using Pollay and Mittal’s (1993) seven-factor belief model. Applying Pollay and Mittal’s seven-factor advertising beliefs model, this study explore the staff of Universiti Sains Malaysia, Penang beliefs and attitudes as well as the demographic characteristics.